Transformations in Social Science Research Methods during the COVID-19 Pandemic - Ryan, J. Michael; Visanich, Valerie; Brandle, Gaspar (The COVID-19 Pandemic Series, 2024)
This volume explores how researchers made innovative use of online technologies to innovate, define, and transform research methodologies in light of the varying impacts of the COVID-19 pandemic, especially those related to the ability to conduct qualitative research. The onset of the COVID-19 pandemic resulted in a radical shift in the way that people all over the world were/have been able to live, work, study, and conduct their daily lives. Academics and other professionals who routinely engage in research were no exception. The sudden, continued, and uneven need for health mandates calling for physical distancing added a particular layer of complexity for those who used research methods that typically required face-to-face interactions. Continued technological developments associated with the Internet had already given rise to ongoing debates on innovative methodological thinking and practices. The COVID-19 pandemic has further accentuated how indispensable the internet has become for the private and public lives of those with access to it, including for their employment, education, leisure, and social interactions. For those fortunate enough to have access to them, communication software such as Zoom and Google Meet have also become indispensable digital resources for researchers seeking to continue conducting research during lockdowns and quarantines, and beyond. More than ever, researchers are finding it useful, even necessary, to equip themselves with online research tools in order to be able to continue conducting their fieldwork. Drawing on research and case studies from around the world, this volume serves as a guidebook for those interested in attuning their own research methods to a world still struggling to grapple with the impacts of the COVID-19 pandemic.